2015
DOI: 10.1016/j.jvsc.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Abnormally high failure rate for femoral angioplasty in patients with pseudoxanthoma elasticum

Abstract: Pseudoxanthoma elasticum (PXE) is an inherited disease characterized by skin lesions, central blindness, and progressive peripheral occlusive disease. Severe claudication is a frequent symptom for which angioplasty represents a possible therapeutic avenue. We report the outcomes of four patients with PXE treated by angioplasty and stenting of the superficial femoral artery in two centers. These patients exhibited an abnormal failure rate for angioplasty and stenting of the superficial femoral artery, suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The prevalence of PAD in our study (29%) did not reach that of the previously reported, possibly due to lack of data: ABIs were available for only eight patients. It is also worth noting that while operative treatment is rarely needed and may even be harmful [ 30 ], two of our patients developed critical limb ischemia and were operatively treated without further thrombotic events [ 31 ]. Despite wide-spread occlusive arterial findings in CTA and MRA in four of the present patients, they suffered only from mild claudication as they continued their walking training.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of PAD in our study (29%) did not reach that of the previously reported, possibly due to lack of data: ABIs were available for only eight patients. It is also worth noting that while operative treatment is rarely needed and may even be harmful [ 30 ], two of our patients developed critical limb ischemia and were operatively treated without further thrombotic events [ 31 ]. Despite wide-spread occlusive arterial findings in CTA and MRA in four of the present patients, they suffered only from mild claudication as they continued their walking training.…”
Section: Discussionmentioning
confidence: 99%
“…PXE is a very rare disease for a vascular surgeon to come across, and there are only a few case reports of surgical treatment for arterial stenosis, showing a high rate of early failure in both endovascular and open repair [4]. The mechanism of postoperative failure is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, reports on interventional therapy for PAD in PXE are rare. A literature search revealed only seven cases published to date [ 106 , 141 , 142 , 143 ]. Carter et al reported one case, with distal occlusion of the left femoral artery, that was successfully treated by femoropopliteal bypass grafting.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Following this, two patients were treated conservatively, because they had potent collateral circulation, and two patients were treated by femoropopliteal bypass grafting. The authors concluded that angioplasty and the stenting of femoral arteries in PXE patients should not be recommended [ 143 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%